Almacenamiento refrigerado y costos de producción de brócoli (Brassica oleracea L. var. italica) y espinaca (Spinacia oleracea L.). - Valencia Merchán, Alvaro; Guerrero Galvis, Jorge R. (Instituto Colombiano Agropecuario, 2018)
Brócoli-Brassica oleracea var. italica